1990
DOI: 10.1111/j.1365-2621.1990.tb01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of ginger rhizome: kinetic studies with dichloromethane, ethanol, 2‐propanol and an acetone—water mixture

Abstract: The kinetics of extraction of [6]-ginger01 from ground Jamaican ginger rhizome have been determined at 30°C in dichloromethane, ethanol, isopropanol and an 80% (v/v) acetone + 20% (v/v) water mixture. The extractions all proceeded in three stages: an initial 'washing' stage, a fast stage and a subsequent much slower stage. The rate of extraction of hexahydrocurcumin in ethanol was found to follow a simpler pattern. From the first order plots, the diffusion coefficients of the extracted solubles within the ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 22 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the amount of phenolic compounds in an extract depends on the solvents used in the extraction process. Among these, methanol was found to have the biggest impact, while acetone had the smallest influence on phenolic compounds’ quantity, which, probably, is related to the solvent’s viscosity [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the amount of phenolic compounds in an extract depends on the solvents used in the extraction process. Among these, methanol was found to have the biggest impact, while acetone had the smallest influence on phenolic compounds’ quantity, which, probably, is related to the solvent’s viscosity [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spiro et al studied kinetics of ginger rhizome extraction with different solvent such as dichloromethane, ethanol, 2-propanol and acetonewater mixture [8]. They reported that the yield of extraction decreased in the sequence acetone, acetone and water, dichloromethane, ethanol, 2-propanol at 30 o C. Tian et al studied the influence of microwave irradiation treatment on the extraction of ginger [9]. Results obtained from their work indicated that the most satisfying results can be achieved by pretreatment of microwave irradiation under the output power of 480 W during 6 min.…”
Section: Introductionmentioning
confidence: 99%